2017
DOI: 10.1177/0004867417707819
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of bullying victimisation and perpetration in a nationally representative sample of Australian youth

Abstract: Bullying continues to be frequently experienced by Australian adolescents. The current findings showed that involvement in any bullying behaviour was associated with increased risk of concurrent mental health problems. This evidence can be used to inform decisions concerning the allocation of resources to address this important health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 38 publications
9
75
1
1
Order By: Relevance
“…As in adolescence, the experience of frequent bullying in childhood relates to poorer mental health. Prior studies with youth (11 + years) have shown that frequent bullying is associated with mental health problems (Bond et al., ; Due et al., ; Ford et al., ; Hodges et al., ; Klomek et al., ; Lien et al., ; Thomas et al., ; Ttofi et al., ; Undheim & Sund, ). The current results with younger children corroborate this concern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in adolescence, the experience of frequent bullying in childhood relates to poorer mental health. Prior studies with youth (11 + years) have shown that frequent bullying is associated with mental health problems (Bond et al., ; Due et al., ; Ford et al., ; Hodges et al., ; Klomek et al., ; Lien et al., ; Thomas et al., ; Ttofi et al., ; Undheim & Sund, ). The current results with younger children corroborate this concern.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of the present study also had interesting divergence from existing knowledge in the field. With older youth, international and Australian research has described a rate of bullying of around 13% (Craig et al., ; Forero et al., ; Rigby & Johnson, ; Thomas et al., ). With younger children, in the present study the rate of frequent bullying was much higher at 29%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consider still the transgenerational (epigenetic) effects of stress and mental illness [56], and beyond brain and behavior disorders, it is almost impossible to calculate the societal burden of small-and large-scale aggression and incivility [57][58][59]. In a vicious cycle, both victim and perpetrator are on a trajectory to depression, isolation, and ill-health [60][61][62].…”
Section: Mars Colonies and Intellectual Escapismmentioning
confidence: 99%